REVIEW ARTIKEL: PEMANFAATAN GLUKOMANAN UMBI PORANG SEBAGAI EDIBLE FILM DENGAN PENAMBAHAN EKSTRAK TANAMAN SEBAGAI AGEN ANTIBAKTERI DAN ANTIOKSIDAN - Amanda Salwa Nur Azizah; Subur P. Pasaribu; Aman Sentosa Panggabean (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
The increasing global production of plastics has caused serious environmental impacts due to their non-degradable nature. Therefore, eco-friendly packaging alternatives such as edible films (EF) based on natural biopolymers are needed. Glucomannan derived from porang tubers (Amorphophallus muelleri Blume), also known as Konjac Glucomannan (KGM), is one of the most promising biomaterials because it is biodegradable, non-toxic, and easily forms elastic films. The purpose of this review is to examine the potential of glucomannan as a base biomaterial for EF and the role of adding plant extracts as antibacterial and antioxidant agents. The review was conducted through an analysis of recent literature on the physical, chemical, and functional characteristics of KGM-based EF with the addition of natural bioactive compounds. The results show that the combination of glucomannan and plant extracts enhances the mechanical properties, water vapor resistance, and antibacterial activity of the film. In addition, the antioxidant activity increases with the incorporation of phenolic and flavonoid compounds, which effectively suppress oxidation and extend the shelf life of food products. Overall, KGM-based EF enriched with plant extracts has strong potential as an active and functional packaging material that supports sustainability and could replace conventional plastics in the future Keywords: glucomannan; tuber porang; edible film; antimicrobial; antioxidant.